2015
DOI: 10.5455/medarh.2015.117-122
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Level and Hemodynamic Changes During Tooth Extraction at Hypertensive and Normotensive Patients

Abstract: Background:The patients that are subjects to oral-surgical interventions produce large amounts of steroids in comparison with healthy patients which are not a subject to any dental intervention. The aim of research was to determine the level of stress hormone cortisol in serum, arterial blood pressure and arterial pulse, and to compare the effectiveness of the usage of lidocaine with adrenalin in comparison with lidocaine without adrenalin during the tooth extraction.Patients and methods:This clinical research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…Agani et al reported a significant correlation between extraction of teeth and hemodynamic changes including both the blood pressure and pulse rate, regardless of the presence or absence of a vasoconstrictor in the local anaesthesia. These findings have to be evaluated further in future studies due to inconsistent evidence ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agani et al reported a significant correlation between extraction of teeth and hemodynamic changes including both the blood pressure and pulse rate, regardless of the presence or absence of a vasoconstrictor in the local anaesthesia. These findings have to be evaluated further in future studies due to inconsistent evidence ( 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…The stress before the injection of anaesthetic produces more fear than the actual injection. Previous studies have shown, the increase in systolic and diastolic blood pressure among individuals who underwent extraction regardless of the anaesthetic used, with or without vasoconstrictor, while no significant difference was seen with respect to pulse rate ( 8 ).…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies have described increases in blood pressure (BP) and heart rate (HR) following the infiltration of local anesthesia with VC ( 6 , 7 ). Electrocardiographic (ECG) alterations have also been associated with patient anxiety in the context of dental treatment ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…In literature, various scales are documented to measure the anxiety of dental patients, of which Corah's Dental Anxiety Scale is the most often used. Other scales such as the Modified Corah Dental Scale, Charles Spielberger Psychologist Scale, KDFS, ISAR, Modified Dental Anxiety Scale,[ 9 ] and Gatchel's Anxiety Scale have also been used. In previous studies conducted by Gatchel's[ 10 ] Chanpong et al .…”
Section: Discussionmentioning
confidence: 99%